Quality Assurance in the Japanese Universities - Sorin-George Toma; Shinji Naruo (Amfiteatru Economic Journal, 2009)
The higher education system represents a vital means for a country to nurture its economic development and social cohesion. All over the world there has been an increasing interest in quality assurance (QA) in higher education, reflecting both the growing importance of higher education services and their valuable contribution to societies. As higher education services moves beyond national borders, the need for international cooperation in QA have increased in the last decades. Moreover, there is an internationalization of QA in higher education and the Asia-Pacific region is a good example. The paper examines the current academic literature surrounding QA in higher education in Asia-Pacific region, emphasizing the case of Japan. Based both on literature review and the experience of a Japanese visiting professor the paper deals with the emergence and development of QA systems in higher education in Asia-Pacific region and focuses on the case of the Japanese higher education system (JHES). The paper shows that the need for international arrangements and approaches to QA in higher education is clearly demonstrated by the case of Asia-Pacific region. It also shows that, facing the challenges of a highly competitive knowledge driven global economy, the region has begun to establish and implement an agreed set of QA principles in higher education. Commitment to quality by all higher education providers from the region has proved to be essential. The importance of quality provision in cross-border higher education made the JHES to implement a new approach in QA.
Keywords: I20; 330; quality assurance; higher education; Asia-Pacific region; Japanese higher education system; Japan